Tailored Cytokine Optimization for ex vivo Culture Platforms Targeting the Expansion of Human Hematopoietic Stem/Progenitor Cells - Branco, André; Bucar, Sara; Moura-Sampaio, Jorge; Lilaia, Carla; Cabral, Joaquim M. S.; Fernandes-Platzgummer, Ana; Lobato da Silva, Cláudia (Frontiers in Bioengineering and Biotechnology, 2020)
Umbilical cord blood (UCB) has been established as an alternative source for hematopoietic stem/progenitor cells (HSPC) for cell and gene therapies. Limited cell yields of UCB units have been tackled with the development of cytokine-based ex vivo expansion platforms. To improve the effectiveness of these platforms, namely targeting clinical approval, in this study, we optimized the cytokine cocktails in two clinically relevant expansion platforms for HSPC, a liquid suspension culture system (CS_HSPC) and a co-culture system with bone marrow derived mesenchymal stromal cells (BM MSC) (CS_HSPC/MSC). Using a methodology based on experimental design, three different cytokines (stem cell factor (SCF), fms-like tyrosine kinase 3 ligand (Flt-3L) and thrombopoietin (TPO)) were studied in both systems during a 7-day culture under serum-free conditions. Proliferation and colony-forming unit assays, as well as immunophenotypic analysis were performed. Five experimental outputs (fold increase (FI) of total nucleated cells (FI TNC), FI of CD34+ cells, FI of erythroid burst-forming unit (BFU-E), FI of colony-forming unit granulocyte-monocyte (CFU-GM) and FI of multilineage colony-forming unit (CFU-Mix)) were followed as target outputs of the optimization model. The novel optimized cocktails determined herein comprised concentrations of 64, 61 and 80 ng/mL (CS_HSPC) and 90, 82 and 77 ng/mL (CS_HSPC/MSC) for SCF, Flt-3L and TPO, respectively. After cytokine optimization, CS_HSPC and CS_HSPC/MSC were directly compared as platforms. CS_HSPC/MSC outperformed the feeder-free system in 6 of 8 tested experimental measures, displaying superior capability towards increasing the number of hematopoietic cells while maintaining the expression of HSPC markers (i.e. CD34+ and CD34+CD90+) and multilineage differentiation potential. A tailored approach towards optimization has made it possible to individually maximize cytokine contribution in both studied platforms. Consequently, cocktail optimization has successfully led to an increase in the expansion platform performance, while allowing a rational side-by-side comparison among different platforms and enhancing our knowledge on the impact of cytokine supplementation on the HSPC expansion process.